2020
DOI: 10.1128/jvi.00251-20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pigment Prodigiosin Demonstrates a Unique Antiherpesvirus Activity That Is Mediated through Inhibition of Prosurvival Signal Transducers

Abstract: Herpes simplex virus (HSV) is among the most prevalent viral infections worldwide and remains incurable. While nucleoside analogs are used to relieve symptoms of infection, they suffer from having serious adverse effects and are unable to abolish the virus from the host. Here, we demonstrate a unique antiviral effect of prodigiosin (PG), a natural secondary metabolite produced by Serratia marcescens, on HSV infection. We show that PG naturally exerts antiviral activity against HSV-1 and HSV-2 infections. PG tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
(44 reference statements)
0
20
0
2
Order By: Relevance
“…Most of the current drugs used to treat HSV are nucleoside analogues, which have a high incidence of side effects and target DNA replication. Fortunately, recent studies have identified several promising and safer drugs that target the AKT signalling pathway to inhibit HSV infection in the cornea, including the natural secondary metabolite prodigiosin (PD), which is produced by Serratia marcescens , and a selective 3-phosphoinositide-dependent kinase 1 inhibitor called BX795 [ 108 , 109 ]. And the inhibitory effect of PD on HSV-1 in vivo, in vitro, and ex vivo, with positive therapeutic results observed in mouse models.…”
Section: Diseases Their Therapies and Akt In Cecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current drugs used to treat HSV are nucleoside analogues, which have a high incidence of side effects and target DNA replication. Fortunately, recent studies have identified several promising and safer drugs that target the AKT signalling pathway to inhibit HSV infection in the cornea, including the natural secondary metabolite prodigiosin (PD), which is produced by Serratia marcescens , and a selective 3-phosphoinositide-dependent kinase 1 inhibitor called BX795 [ 108 , 109 ]. And the inhibitory effect of PD on HSV-1 in vivo, in vitro, and ex vivo, with positive therapeutic results observed in mouse models.…”
Section: Diseases Their Therapies and Akt In Cecsmentioning
confidence: 99%
“…And the inhibitory effect of PD on HSV-1 in vivo, in vitro, and ex vivo, with positive therapeutic results observed in mouse models. PD treatment may inhibit the phosphorylation of AKT in CECs, preventing it from inactivating GSK3β, blocking apoptosis, promoting protein synthesis, and creating a host environment that facilitates viral replication [ 109 ]. Moreover, BX795 inhibits the PI3K/AKT/mTOR pathway and then blocks the hyperphosphorylation of eukaryotic initiation factor 4E-binding protein 1, which is a member of a family of translation repressor proteins [ 110 , 111 ].…”
Section: Diseases Their Therapies and Akt In Cecsmentioning
confidence: 99%
“…Another interesting study recently performed by Suryawanshi et al . evaluated the antiviral activity of PG against Herpes simplex virus (HSV) 1 and 2 [ 121 ]. It was observed that 2.5 µM PG strongly inhibited HSV-1 infection in human corneal epithelial (HCE) cells, a physiologically relevant in vitro model.…”
Section: Biological Activities Of Prodigiosinmentioning
confidence: 99%
“…Prodigiosin also demonstrates activity against chloroquine-resistant strain Plasmodium falciparum , induces synthesis of autolysins in Bacillus cereus, and stimulates production of ROS that prevents formation of biofilm in P. aeruginosa [56] , [59] . In the case of herpes simplex virus type 1 and 2, prodigiosin exerts antiviral activity by inhibiting NF-κB and Akt signaling pathways in vitro and ex vivo in cultured porcine corneas [60] . The pathway in which prodigiosin provides antiviral relief involves the inhibition of anti-apoptotic activity of TNF-α mediated by NF-κB [60] .…”
Section: Spectrum Of Bacterial Pigmentsmentioning
confidence: 99%
“…In the case of herpes simplex virus type 1 and 2, prodigiosin exerts antiviral activity by inhibiting NF-κB and Akt signaling pathways in vitro and ex vivo in cultured porcine corneas [60] . The pathway in which prodigiosin provides antiviral relief involves the inhibition of anti-apoptotic activity of TNF-α mediated by NF-κB [60] . Applications: Prodigiosin has been used in food coloration to replace the synthetic pigments used in the food industry, coloration of polyolefines, as well as applied in sunscreen to increase the sunscreen protection factor [61] .…”
Section: Spectrum Of Bacterial Pigmentsmentioning
confidence: 99%